Rethinking the allocation of MBG funds: Toward justice, utility, and national benefit - Taufikin Taufikin (Priviet Social Sciences Journal, 2026)
The "Meal-Based Grant (MBG)" is an education welfare package, which is concurrently provided to all students without differentiation by their family's economic condition, and is typical. While this policy intends to promote equity, there is a risk of waste and unfair distribution if financially advantaged students can access their entitlements from the public purse based on financial means rather than need. This study critically examines the MBG scheme from the perspectives of social justice, maqāṣid al-sharīʿah, and sustainable development. Applying normative-analytical and comparative policy reflection, the study argues that the MBG must be redesigned with greater focus. From there, the model works through a school-level targeting approach to serve only poor, underprivileged, and orphaned children directly. Furthermore, the remaining funds will be transferred for strategic educational investments, such as long-term scholarships at least up to the level of undergraduate studies, school infrastructure upgrading, merit-based awards, and research and innovation funds that include funding student inventions up to patent and industrial realization. Redistribution meets both fairness and efficiency requirements and raises a country's competitive ability and overall social welfare. The transformation from short-term to long-term consumption under the reformed MBG scheme will contribute more effectively to the SDGs: quality education and innovation. Finally, this study offers a new policy direction to strengthen short-run welfare forces through long-term human capital development.